Modeling employments rate data using ordinal logistic regression - Fitrianto, Anwar; Ab. Ghazab, Maziatul Izati (IDOSI Publications, 2014)
In 2007-2008, there are huge recession occur in employment rate. It is corresponding to a global economic crisis on that had a huge effect on the number of employment people around the world. According to International Labour Organization (ILO), the number of person who has loss their job increased from 178 million in 2007 to 197 million in 2012, with a peak of 212 million reached in 2009. In our study, we are interested to use logistic regression analysis to determine the factors which are considered to be a significant contributor to the employment. The logistic regression model was used to build models for nine independent variables which are urban population, inflation rate, literacy rates, health expenditure, spending on education, labour participation rate, agriculture expenditure, health index and human development index.